Mathematical modeling of the optimum planning электромонтажных functioning - Литвиненко, О. Є.; Цивінський, К. В. (Problems of Informatization and Control, 2007)
To solve the task of implementation of maximal amount of wiring works on minimum time the special purpose functions are formalized. The system of limitations, which represents the requirements to the financial and technical providing of wiring process, is described and formulated. It is also proved that the specified mathematical problem definition falls under the category of extreme combinatorial problem with a linear structure, accordingly allows applying the method of the directed search of variants at its decision